Using Objects and Patterns to Implement Domain Ontologies - Guizzardi, Giancarlo; Falbo, Ricardo de Almeida; Pereira Filho, José Gonçalves (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de Software, 2001)
Ontologies are becoming an important mechanism to build information systems. Nevertheless, there is still no systematic approach to support the design of such systems using tools that are common to information systems developers. In this paper, we propose an approach for deriving object frameworks from domain ontologies and then we show the application of this approach in the software process domain.